Maternal and perinatal outcome in instrumental vaginal deliveries over 5 years: a retrospective study - Ghanchi, Fatima M.; Mansuri, Misbah I.; Doshi, Haresh U.; Kharod Patel, Prarthana H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Due to fear of trauma and less skill, use of instrumental vaginal delivery (IVD) is decreasing every year and incidence of caesarean section is increasing. Caesarean section is a major surgery associated with increased morbidity and mortality. This study evaluates the incidence of instrumental vaginal delivery and associated maternal and perinatal outcome. Methods: This observational retrospective study was carried out in full term antenatal patients in labour with vertex presentation who had undergone operative vaginal deliveries during the study period from January 2017 to December 2021 at G.C.S. Hospital. Data were obtained from the hospital records and analysed which included the age, parity, incidence, indication, the APGAR scores of the babies and complications in the patient. Results: Incidence of instrumental deliveries was found to be 1.98%. Most common indications for IVD were prolonged second stage of labour followed by foetal distress and post-dated pregnancy. Most common maternal complication was perineal tears and most common perinatal complication was neonatal intensive care unit (NICU) admission. Conclusions: The decision to proceed with an operative vaginal delivery when a spontaneous vaginal delivery is not possible must be based upon maternal and foetal factors. Most common maternal complications were perineal tears, cervical tears, episiotomy extension, vaginal laceration and atonic postpartum hemorrhage (PPH). Most common neonatal complications were NICU admission most commonly for neonatal hyperbilirubinemia.